Complete Closed-Loop Ventilatory Circuit Delays the Onset of Ventilator-Associated Pneumonia in Mechanically Ventilated Neurological Patients in the ICU: A Single-Center Prospective Preliminary Study - Archana K. Raichurkar; V.J. Ramesh; Rohini M. Surve; H.B. Veena Kumari; Dhritiman Chakrabarti (Journal of Neuroanaesthesiology and Critical Care)
Background Ventilator-associated pneumonia (VAP) is preventable yet its incidence remains high. We compared conventional ventilator circuit with open suction and dual heated wire circuit (DHWC) with closed suction on the incidence of VAP.